Classroom Techniques To Develop Students English Speaking Skill: A Naturalistics Study At Smp Muhammadiyah 1 Surakarta - Prapyuningrat, Ayu Hertika; , Prof. Dr. Endang Fauziati, M. Hum (2016)
This study is aimed in describing (1) Classroom technique used by the teacher in Teaching English at SMP Muhammadiyah 1 Surakarta (2) The purposes of each classroom technique (3) The students' role (4) The teachers' role. This type of the research is descriptive qualitative research especially naturalistic. The method of collecting data are observation, interview, and documentation. The result is some classroom techniques used by the teacher to develop students' English skill, especially speaking skill such as question and answer in group, conversation practice, discussion, role play, playing cards, picture describing, retelling video, and storytelling. The teacher has roles such as teacher as controller, teacher as organizer, teacher as prompter, teacher as resource, teacher as tutor, teacher as observer, and teacher as model. The student has roles such as student as planner, student as group, student as tutor, student as monitor and evaluator. The conclusion of this research is that the English teacher at SMP Muhammadiyah 1 Surakarta used various classroom techniques in the teaching-learning process that can develop the students' English Speaking skill. The various classroom techniques make the students interested and enjoy in learning English language. Therefore, the student will not be bored and lazy in the class. The students can understand the material, the students become more active and creative, especially in learning speaking skill and the student can interested, so the student enjoys in learning English speaking skills. Key word: Classroom technique, speaking skill, teachers' roles, students' roles.